Transumbilical Single-Site Laparoscopic Intraperitoneal Closure of the Internal Inguinal Ring for Pediatric Inguinal Hernia - Ji, Yi; Li, Yanan; Zhang, Xuepeng; Qiu, Tong; Chen, Siyuan; Xu, Zhicheng (Frontiers in Pediatrics, 2022)
Background: A new novel technique for pediatric inguinal hernia (PIH) repair, namely, transumbilical single-site laparoscopic intraperitoneal closure (TUSLIC) of the internal inguinal ring (IIR) with a single instrument, was introduced. The short-term follow-up of TUSLIC for PIH was compared with that of transabdominal multiple-site laparoscopic extraperitoneal closure (TAMLEC) for PIH. Methods: Patients who underwent TUSLIC with a single instrument and those who underwent TAMLEC were assigned to group A and group B, respectively. Descriptive variables, perioperative clinical features and short-term outcomes were retrospectively analyzed and compared between the two groups. Results: In total, 289 patients were enrolled in this study. Of these, 190 patients who received TUSLIC were included in group A, and 99 patients who received TAMLEC were included in group B. The descriptive variables (including sex, age, weight, preoperative diagnosis of patients) were comparable between the two groups (P>0.05). The mean operative times for unilateral hernia repair and bilateral hernia repairs in group B were significantly less than those in group A (P<0.05). The values of surgical site infection, umbilical bleeding, testicular atrophy, iatrogenic ascent of the testis and secondary hydrocele were not significantly different between the two groups. There were no suture granulomas, and recurrence occurred in group A, though at a significantly lower rate than in group B (P<0.05). Conclusions: TUSLIC is a feasible and reliable minimally invasive method for PIH. TUSLIC has the advantages of minimized complications, a low recurrence rate and satisfactory cosmetic appearances.